1982
DOI: 10.1177/000348948209100310
|View full text |Cite
|
Sign up to set email alerts
|

Vocal Quality, Articulation and Audiological Characteristics of Children and Young Adults with Diagnosed Allergies

Abstract: This study details vocal quality, articulation errors, and hearing disorders in 80 children and young adults with diagnosed allergies. Results indicated that almost 50% had abnormalities in vocal quality and/or articulation and 13% had reduced auditory acuity. Vocal quality disorders showed a significant relationship to bronchial asthma in association with other allergic reactions. All subjects with diminished hearing had allergic rhinitis either singly or in combination with another disorder. Findings suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 9 publications
2
16
0
Order By: Relevance
“…The symptoms and signs of provoked change in vocal functioning were breathy voice quality, perceptually decreased inten sity of the voice and the failure of the glottis to close completely. The results were in ac cordance with observations that low vocal intensity and breathiness may be associated with respiratory allergies [Maximov and Moskov, 1981;Baker et al" 1982], Allergic edema formation and an increase in the volume of the vocal cords were not distinctly observed in this study, but a very low increase may escape notice in a mirror examination [Sonninen. personal commun., 1983], Slight dysphonia due to a slight in crease in vocal cord volume may not even affect the auditory impression, although it can be observed in a spectral analysis [Son ninen and Hurme, 1981], The significant skin test positivity of the clinical group indicates atopy.…”
Section: Discussionsupporting
confidence: 91%
“…The symptoms and signs of provoked change in vocal functioning were breathy voice quality, perceptually decreased inten sity of the voice and the failure of the glottis to close completely. The results were in ac cordance with observations that low vocal intensity and breathiness may be associated with respiratory allergies [Maximov and Moskov, 1981;Baker et al" 1982], Allergic edema formation and an increase in the volume of the vocal cords were not distinctly observed in this study, but a very low increase may escape notice in a mirror examination [Sonninen. personal commun., 1983], Slight dysphonia due to a slight in crease in vocal cord volume may not even affect the auditory impression, although it can be observed in a spectral analysis [Son ninen and Hurme, 1981], The significant skin test positivity of the clinical group indicates atopy.…”
Section: Discussionsupporting
confidence: 91%
“…19,21 Inhaled asthma medication has the potential to directly affect the larynx, and therefore asthma, or its treatment, may have a direct effect on patients' voices. Up to 50 per cent of patients taking inhaled corticosteroids may suffer from dysphonia 28 which is usually reversible. 29 This has been attributed to fungal infection or steroid-induced adductor myasthenia of the larynx, 30 although laryngoscopy or voice laboratory assessment may reveal more complicated abnormalities such as apposition abnormalities and cycle to cycle irregularity.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the voice literature is focused on those patients who attend otolaryngology clinics; however, Baker et al found that 50 per cent of 80 young adults with asthma or allergy had vocal quality abnormalities (as assessed by speech and language therapists). 6 Voice morbidity in patients with asthma has not been extensively studied.…”
Section: Introductionmentioning
confidence: 99%